A Stretchable Highoutput Triboelectric Nanogenerator Improved by MXene Liquid Electrode with High Electronegativity. (13th September 2020) - Cao, Wen‐Tao; Ouyang, Han; Xin, Wei; Chao, Shengyu; Ma, Chang; Li, Zhou; Chen, Feng; Ma, Ming‐Guo
Abstract: Growing demand in intelligent wearable electronics raises an urgent requirement to develop deformable and durable power sources with high electrical performance. Here, a stretchable and shape‐adaptive triboelectric nanogenerator (TENG) based on a MXene liquid electrode is proposed. The open‐circuit voltage of an MXene‐based TENG reaches up to 300 V. The excellent fluidity and highly electronegativity of the MXene liquid electrode, gives the TENG long‐term reliability and stable electrical output regardless of diverse extreme deformations. With harvesting mechanical energy from hand tapping motion, the TENG in a self‐charging system can charge up capacitors to drive wearable electronics. Moreover, the TENG can be attached to both human skin and clothes as a human motion monitoring sensor, which can inspect the frequency and amplitude of various physiological movements. This work provides a new methodology for the construction of stretchable power sources and self‐powered sensors, which have potential applications in diverse fields such as robotics, kinesiology, and biomechanics. Abstract : A stretchable and shape‐adaptive triboelectric nanogenerator (TENG) based on a MXene liquid electrode is proposed. The TENG possesses outstanding output performance under various deformations, such as stretching, folding, and twisting. Furthermore, the flexible MXene‐based TENG, which can be used for biomechanical energy harvesting and self‐powered motion monitoring, has potential applications in soft robotics, green energy sources, human‐machine interactions, and wearable electronics.